Analisis Ekonomi Menurun dan Suku Bunga Besar terhadap Kredit Macet pada Koperasi Permodalan Nasional Madani Mekar, Kabupaten Brebes - Rita Isnaeni; Nasiruddin; Andi Yulianto; Nur Afridah; Anisa Sains Kharisma (Universitas Muhadi Setiabudi, 2020)
Bad debts are often a problem in financial institutions, both government-owned and privately owned financial institutions, because they can interfere with the company's operations. Mekar's National Madani Capital (PNM) as a state-owned financial institution must also understand what aspects can encourage bad debts. The purpose of this study was to analyze the effect of declining economies and large interest rates on bad debts at the PNM Mekar cooperative, Brebes. This study used primary data and the study used was multiple linear regression analysis. The results of the study prove that simultaneously the economy grows and interest rates can affect bad debts and both can explain credit strongly. Partially the economy grew insignificantly on bad debts while interest rates had a significant direct effect on bad debts.